INOVASI DESAIN PEMANFAATAN LIMBAH SERBUK KAYU YANG DIGUNAKAN UNTUK MENINGKATKAN NILAI ESTETIS DAN EKONOMIS PADA MASYARAKAT - Abdul Saefullah (Pusat Riset dan Inovasi Nasional, 2022)
Organic waste is a kind of waste that much cause pollution, although this type of waste can be recycled by nature but still cause problems if left unchecked . Wood, for an example we bring here, is a natural resource that is widely used by humans , especially in Indonesia for home furnishings and interior elements ( home accessories ). From the process of making furniture it produced a lot of waste, a kind of sawdust called gerajen (java) and it only ended up to burned (incinerate) or even left to rot away. The problems that exist are lack the utilization of sawdust waste that can be transformed to product to add to the aesthetic and economic values , the lack of utilization of waste product development and innovation shape as well as to cultivate and experiment through design innovation for sawdust utilization into a product. The objective of this research are to bring both aesthetic and economic value of sawdust waste as an effort to reduce pollution resulting from incineration of sawdust , provides new insights for the processing of waste, sawdust as alternative materials to create a product that the added value aesthetically and economically. The methods undertaken through several processes such as obtained from trials or experiments. From variety of data obtained would lead us to design concept of finished product, doing some experiments processing sawdust mixed with some other material to produce a product that can provide added value to the waste.